Left internal mammary artery side branch intervention in the management of coronary steal syndrome following coronary artery bypass grafting. Issue 1 (29th November 2019) - Mangels, Daniel; Penny, William; Reeves, Ryan
Abstract: Objective: The objective of this qualitative review is to summarize the pathophysiological and clinical data behind the clinical entity of left internal mammary artery (LIMA) side branch coronary steal as well as the potential diagnostic and therapeutic modalities available. Background: The presence of persistent unligated LIMA side branches following coronary artery bypass grafting has previously been associated with stable angina and acute coronary syndromes. However, despite numerous attempts to objectively demonstrate a coronary steal phenomenon, the pathophysiology of LIMA side branch flow diversion remains elusive and the clinical utility of intervention is not well elucidated. Methods: A review of literature and available data including case reports, case series, and investigational studies was performed. Results: Therapeutic closure of LIMA side branches has been reported in at least 44 patients and in at least 31 publications since 1990 and is associated with an 87.5% rate of freedom from angina amongst technically successful initial interventions. In all patients with pre‐ and post‐ stress testing, intervention was associated with an improvement and/or resolution of previously observed reversible ischemia. Conclusions: LIMA side branch coronary steal should remain an ongoing consideration in symptomatic patients with large unligated side branches on angiography, particularly when there is clear evidence of reversible ischemic on perfusion imaging.